Chemical Composition Analysis of Citrus×limon (L) Osbeck Leaf Essential Oil and Its Activity as an Anti-Cervical Cancer Agent - Afif, Iffat Syafiqoh; Suryati, Suryati; Santoni, Adlis (Universitas Pendidikan Mandalika, 2024)
Cervical cancer is a life-threatening disease. The use of synthetic drugs for its treatment can have serious adverse effects on the body. Therefore, it is necessary to search for natural drugs that are safe for the body. One of the secondary metabolites contained in plants is essential oils (EO), EO are known to have activity as anti-cervical cancer. Genus Citrus is known for containing EO compounds, one of the species of the genus is Citrus×lemon (L) Osbeck. The purpose of this study is to identify the chemical components of the EO isolated from the leaves of C×limon and to evaluate its cytotoxic activity against cervical cancer. EO was isolated from C×limon leaves collected in Padang City, Indonesia using the hydrodistillation method. EO was then analyzed by GC-MS. To determine its cytotoxicity, BSLT was conducted, followed by molecular docking and MTT assays. The experiment yielded a yellow liquid with a density of 0,8684 g/mL and a yield of 0,181%. GC-MS analysis of the EO identified 56 chemical components, with the main compounds are (-)-β-pinene (7.32%), (-)-limonene (28.40%), geranial (5.54%), caryophyllene (5.22%). The EO showed high toxicity against Artemia salina L larvae, with an LC50 value of 3,697 µg/mL. Through molecular docking, it is known the (-)-limonene, geranial, (-)β-pinene and caryophyllene compounds as the main compounds in of EO are known to bind to form complexes with cervical cancer proteins (HPV18E6). MTT assay showed weak cytotoxic activity of EO against HeLa cells, with an IC50 of 218.9 µg/mL.